THE EFFECT OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT & TRANSACTIONAL LEADERSHIP ON JOB SATISFACTION AT PT PUTRA PERKASA ABADI - Pramestry, Ditha; Agustina, Tri Siwi; Ekowati, Dian (PT Naureen Digital Education, 2024)
This study examines the relationship between organizational culture, work environment, and transactional leadership on job satisfaction at PT Putra Perkasa Abadi (PPA). The sample consisted of 80 workers. Questionnaire tabulation, validity, and reliability tests were used for analysis. Multiple linear regression was used for data analysis. The findings indicate that organizational culture can increase job satisfaction, and there is a positive relationship between organizational culture and job satisfaction. A positive influence of work environment on job satisfaction was also found. Moreover, a positive influence between transactional leadership and job satisfaction was discovered. Therefore, strengthening organizational culture, improving the work environment, and applying a transformational leadership style can increase job satisfaction and performance at PPA. Understanding and applying these concepts can improve employee satisfaction and loyalty.